Inhibition of in vitro lymphocyte blastogenesis by inhibitor produced by cultured human lymphoblasts - Hersh, E. M. (1974)
Normal human lymphoblastoid cell lines, growing in continuous suspension culture, produce inhibitors of in vitro lymphocyte blastogenesis. The inhibitor reduces human lymphocyte blastogenic responses to phytohaemagglutinin, streptolysin-O and the mixed lymphocyte culture 90–99%, is non-cytotoxic and can inhibit both newly initiated and on-going responses. The inhibitor is heat-stable at 80°C but labile at 100°C, non-dialysable and degraded by pronase but not DNase or RNase. It is species- and tissue-specific and does not inhibit the proliferation of mouse lymphocytes, human melanoma cells or human bone marrow in vitro colony-forming cells. Inhibitor was produced only under very specific conditions of crowding. Thus, maximal inhibitor production occurred at 5 × 10(6) lymphocytes per cm(2) culture surface area while only 0–5% of the maximal amount was produced at 10(6) or 5 × 10(7) lymphoblasts per cm(2). This data is relevant to the nature of feedback control of immunological reactions and may guide the development of new classes of immunosuppressants.